(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The Cenomanian-Coniacian units of the Capriolo - Corno Pendita area belong to the eastern margin of the Lombardy Basin. The Coniacian turbidite sandstone lithosome (Arenarie di Sarnico) unconformably overlies the Cenomanian-Turonian units. The unconformity should be due to slumping and sliding during Late Turonian time. The Arenarie di Sarnico seal the geometries related to the Cenomanian - Turonian synsedimentary tectonic. Evidences for this activity are provided by slumpings and chaotic beds (Early-Late Cenomanian) and by unconformities predating the submarine erosion phase.